(untitled) (Academicia Globe: Inderscience Research, 2023)
The article explores the process of applying interactive teaching methods in mathematics lessons. It is concluded that a math teacher becomes an active participant in the educational process. Interactive methods allow you to conduct classes with greater spontaneity, emotional recovery due to the absence of complex electronic and mechanistic technologies and tools. Interactive learning has a positive effect both on improving the quality of knowledge and on improving students’ performance and interest in the subject. Students learn to apply their knowledge in new situations, learn to use them in practice and to extract them. They learn to communicate, make friends, be merciful, attentive to each other - this is also the result of educational cooperation.